Le projet du bonheur conjugal dans Le Mesnagier de Paris - Loba, Anna (Studia Romanica Posnaniensia, 2003)
Mesnagier de Paris, drafted in 1393 by an unknown bourgeois person for his young wife, is considered as the most famous medieval treaty concerning the education of women. The happiness is not the main subject of Mesnagier; it is not even evoked in a direct way. The happiness or bliss remains an objective presupposed by the advice given to the young wife. The main purpose of all the eductation is order. The happiness is its corollary. The vision of bliss sketched in Mesnagier de Paris concentrates around the image of the house. The project of the bourgeois authors thus is to build through the structure of the domestic space in its materiał and symbolic dimension a vision of the deserving and honest life. The conception of happiness is based on an at the same time medieval and bourgeois vision of the world. The idea of the stable and unchanging character of the relations between the sexes and that of the ambivalent naturę of women - are medieval. However the ecstasy of conjugal happiness softens in a sensitive way the usual moralizing rhetoric. The need of prosperity and materiał comfort, declared openly, is connected to the urban culture that gets ready for the splendors of the Renaissance.